Analysis of Obstacles and Difficulties of the Academic Ability Test (AAT) on Mathematics Material in Senior High Schools - Jitu Halomoan Lumbantoruan (International Journal of Mathematics and Science Education, 2026)
Lack of student preparation in facing the Academic Ability Test (AAT) in mathematics material. Urgent research on high-level thinking skills in academic preparation of AAT students. The aim is to analyze obstacles, learning difficulties, influencing factors and a strategy model for improving AAT preparation. A quantitative approach with a survey method of 250 high school students selected through proportionate stratified random sampling. Data were collected with a five-point Likert scale questionnaire and analyzed using Structural Equation Modeling (SEM) assisted by SmartPLS. The results showed a good fit model (RMSEA = 0.048; CFI = 0.962; TLI = 0.957) with the ability to explain preparation for facing AAT R² = 0.704. Internal barriers influence learning difficulties (β = 0.487; p < 0.001), external barriers (β = 0.321; p < 0.001), learning difficulties reduce mathematical reasoning ability (β = −0.598; p < 0.001) and AAT preparation (β = −0.316; p < 0.001), mathematical reasoning ability improves AAT preparation (β = 0.534; p < 0.001). It was found that internal barriers are the dominant factor that influences student preparation. In conclusion, preparation for AAT requires strengthening motivation, mathematical reasoning and a conducive learning environment. Implications, teachers and schools need to develop problem-based learning, formative assessment and learning models oriented towards higher-order thinking skills.